Reduced expression of L-selectin in T-cells correlates with relative lymphocyte increase in patients with RRMS treated with natalizumab - functional implication towards PML risk. (3rd March 2020) - Boziki, Marina Kleopatra; Karapanayotides, Theodoros; Papadopoulos, Georgios; Lagoudaki, Roza; Melo, Pamela; Bakirtzis, Christos; Nikolaidis, Ioannis; Gounari, Evdoxia; Tsavdaridou, Vasiliki; Skoura, Lemonia; Afrantou, Theodora; Tatsi, Theano; et al.
ABSTRACT: Objectives: Natalizumab (NTZ), a treatment indicated for patients with highly active Relapsing – Remitting Multiple Sclerosis (RRMS), is known to induce increased relative frequency of lymphocytes. Progressive Multifocal Leukoencephalitis (PML) is a rare but serious adverse event related to NTZ. Moreover, reduced L-selectin (CD62L) expression in T-cells in cryopreserved samples of patients with RRMS under NTZ has been proposed as a biomarker of pre-PML state. We explore the association between L-selectin expression in T-cells and hematological parameters in freshly processed samples of patients with RRMS under NTZ. Methods: We studied L-selectin expression in patients with: RRMS under NTZ (n=34), fingolimod (FTY, n=14), interferon-beta (IFNβ, n=22), glatiramer acetate (GA, N=17); in 9 patients with secondary progressive (SP) MS and in 6 healthy controls. Twenty-two patients under NTZ and 6 patients under FTY were followed for 18 months. One NTZ-treated patient developed PML during the study. Results: Patients under NTZ exhibited increased relative frequency of lymphocytes (40.02±1.45) compared to patients under first–line treatment (30.57±1.68, p<0.001) and to patients with SPMS (29±1.56, p=0.02), and a lower mean L-selectin expression in (69.39±1.73) compared to patients under first–line treatment (79.1±1.17, p=0.003). A negative correlation between the relative frequency of CD4+CD62L+ T-cells and the absolute lymphocyte counts (Pearson's r=0.367, p=0.033) was observed. Discussion: We hereby provide mechanistic insight in a possible pathway implicated in NTZ-related PML risk. These results further underline the need for thorough validation of L-selectin expression in T-cells as a potential pre-PML biomarker. GRAPHICAL ABSTRACT: